Patterns of SES Health Disparities Among Older Adults in Three Upper Middle- and Two High-Income Countries (2019)
OBJECTIVES: To examine the socioeconomic status (SES) health gradient for obesity, diabetes, and hypertension within a diverse group of health outcomes and behaviors among older adults (60+) in upper middle-income countries benchmarked with high-income countries. METHOD: We used data from three upper middle-income settings (Colombia-SABE-Bogotá, Mexico-SAGE, and South Africa-SAGE) and two high-income countries (England-ELSA and US-HRS) to estimate logistic regression models using age, gender, and education to predict health and health behaviors. RESULTS: The sharpest gradients appear in middle-income settings but follow expected patterns found in high-income countries for poor self-reported health, functionality, cognitive impairment, and depression. However, weaker gradients appear for obesity, hypertension, diabetes, and other chronic conditions in Colombia and Mexico and the gradient reverses in South Africa. Strong disparities exist in risky health behaviors and in early nutritional status in the middle-income settings. DISCUSSION: Rapid demographic and nutritional transitions, urbanization, poor early life conditions, social mobility, negative health behavior, and unique country circumstances provide a useful framework for understanding the SES health gradient in middle-income settings. In contrast with high-income countries, the increasing prevalence of obesity, an important risk factor for chronic conditions and other aspects of health, may ultimately change the SES gradient for diseases in the future. © The Author(s) 2018. Published by Oxford University Press on behalf of The Gerontological Society of America. All rights reserved. For permissions, please e-mail: journals.permissions@oup.com.